PENGARUH MEMBACA AL-QUR’AN TERHADAP TINGKAT KECEMASAN AKADEMIK PADA SISWA - Mansyur, Zulkifli; Baba, Mastang Ambo; Bandil, Pertiwi Deviria (Institut Agama Islam Negeri (IAIN) Manado, 2024)
ABSTRACTAcademic anxiety is a significant issue among adolescents where high levels of anxiety can have a negative impact on mental well-beings. In an effort to deal with this, a holistic approach such as reading al-Qur'an which prioritizes mental well- being must be applied. This research aims to find out the effect of reading al- Qur'an on the level of academic anxiety on students. This research employed a quantitative approach with simple linear regression analysis involving 61 subjects. Data collection for the academic anxiety variable used the Academic Anxiety Scale adapted from Calhoun and Accocela, while the al-Qur'an reading variable was taken from the raw score of the al-Qur'an reading results of MA Assalaam students. The results of this study found that there was a significant negative correlation between the variable reading the al-Qur'an and academic anxiety with a score of -0.434. Furthermore, the results of the regression analysis show that reading al-Qur'an has a significant effect on academic anxiety (F-13.727 and p <0.05). Reading al-Qur'an makes an effective contribution of 18.9% to students' academic anxiety at MA Assalaam Manado.Key Words: Reading al-Qur’an, Academic Anxiety and Adolescents. ABSTRAKKecemasan akademik merupakan masalah yang signifikan dikalangan remaja dimana tingkat kecemasan yang tinggi dapat berdampak negatif pada kesejahteraan mental. Dalam upaya menghadapi tersebut pendekatan holistik seperti membaca al-Qur’an yang mengutamakan kesejahteraan mental harus diterapkan. Penelitian ini bertujuan untuk mengetahui pengaruh membaca al-Qur’an terhadap tingkat kecemasan akademik pada pelajar. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis regresi linear sederhana yang melibatkan 61 subjek. Pengumpulan data variabel kecemasan akademik menggunakan Skala Kecemasan Akademik yang diadaptasi dari Calhoun dan Accocela, sedangkan variabel membaca al-Qur’an diambil dari raw score hasil membaca al-Qur’an pelajar MA Assalaam. Hasil penelitian ini menemukan bahwa ada korelasi negatif yang signifikan antara variabel membaca al-Qur’an dan kecemasan akademik dengan skor sebesar -0,434. Selanjutnya, hasil analisis regresi menunjukkan membaca al-Qur’an memiliki pengaruh yang signifikan terhadap kecemasan akademik (F=13,727 dan p < 0,05). Membaca al-Qur’an memberikan sumbangan efektif sebesar 18,9% terhadap kecemasan akademik pelajar di MA Assalaam Manado.Kata Kunci: Membaca al-Qur’an, Kecemasan Akademik dan Remaja.